Different phases of hairy black holes in AdS5 space - Giribet, Gaston Enrique (2015)
We investigate the thermodynamics of hairy black holes in asymptotically anti-de Sitter (AdS) space, including backreaction. Resorting to the Euclidean path integral approach, we show that matter conformally coupled to Einstein gravity in five dimensions may exhibit a phase transition whose endpoint turns out to be a hairy black hole in AdS5 space. The scalar field configuration happens to be regular everywhere outside and on the horizon and behaves asymptotically in such a way that respects the AdS boundary conditions that are relevant for AdS/CFT. The theory presents other peculiar features in the ultraviolet, like the existence of black holes with arbitrarily low temperature in AdS5. This provides a simple setup in which the fully backreacting problem of a hair forming in AdS at a certain critical temperature can be solved analytically.